HUBUNGAN PELAKSANAAN DENGAN KEPUASAN PASIEN TENTANG KOMUNIKASI TERAPEUTIK DI IGD RS AISYIYAH KUDUS - Tri Suwarto; Y Yulisetyaningrum (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2020)
Therapeutic communication is an alternative in providing accurateinformation and establishing trusting relationship to the patients so thatpatients will feel satisfaction for the services they received. In EmergencyInstallation of RS Aisyiyah Kudus nurses made communication based ontheir daily working habits/routines and had not completely paid attention totechnical standard communication correctly and properly.To identify the correlation between management and patients’ satisfaction ontherapeutic communication. This study was a descriptive correlational research by means of cross-sectional framework, and employed a total sampling method to obtain description of therapeutic communication management by nurses with atotal number of 22 respondents based on inclusion criteria. Data was takenthrough observation, and to measure the rate of patients’ satisfaction it wasdone through quota sampling with a number of 112 respondents based oninclusion criteria.From the observation result, therapeutic communication managementcompleted by 22 nurses to 112 patients showed that nurses completed highlygood therapeutic communication to 4 (3.6%) patients, completed that ofgood level to 49 (43.8%) patients, completed that of moderate level to 40(35.7%) patients, and completed that poorly to 19 (17%) patients. Based onthe collected questionnaires, it was obtained a description about patients’satisfaction during being hospitalized in emergency installation, in which 9patients (8%) were highly satisfied, 84 patients (75%) were satisfied, 19patients (17%) were less satisfied, none of the patients felt unsatisfied. Thebivariate Spearman Rank resulted in a significant correlation betweenmanagement and patients’ satisfaction on therapeutic communication.Most of nurses in emergency installation had completed therapeuticcommunication fairly well and patients’ satisfaction on therapeuticcommunication was well satisfied, there was a significant correlationbetween management and patients’ satisfaction on therapeuticcommunication.